PENGGUNAAN METODE PEMBELAJARAN INOVATIF MELALUI DEMONTRASI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQH - Husen, Achmad (Jurnal Asy-Syukriyyah, 2023)
Nowadays there are many problems faced by students' decreased interest in learning, even though interest has a big influence on learning, Therefore, to increase interest in learning, it is very necessary to apply learning methods that attract students' interest, so that it is easier to learn and quickly understood in learning. This study aims was to increase students' understanding of the practice of worship in fiqh subjects.The application of innovative learning methods through the demontration strategy is very suitable to be applied in the learning process. The demontration strategy is a learning model that uses examples. This research was conducted at MI Mathla’ul Anwar Kota Dukuh,  Pandeglang Regency. This research was conducted for 2 months, from September to October 2023. The time of this research was carried out in the odd semester of the 2023/2024 school year. This study uses experimental research methods. The type of experiment used is Quasy Experimental, that is, there is a control group However, it cannot provide overall control over external variables that influence the implementation of the experiment. The approach used in this research is a quantitative approach. In the Homogeneity Test, the results obtained were Fcount < Ftable or 1.07 < 2.215, then the data obtained was homogeneous, in the t test the results were obtained tcount=16.07 and table=2.044 so that the Coefficient of Determination obtained a value of 88.36, the contribution of variable X was obtained to the Y variable of 88.36% while the remainder is equal to 11.64% followed by other variables. The conclusion in this research is that the demonstration learning strategy can increase students' understanding in learning, especially in the material of religious practice in fiqh subjects.